The formation of the 'Book' of Psalms reconsidering the transmission and canonization of Psalmody in light of material culture and the poetics of anthologies - Davage, David 1983-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2016)
Cover -- Preface -- Table of Contents -- Part I: Framing the Task at Hand -- Chapter 1: The Problem -- A. Wilson's New Framework -- B. Sketching Major Trajectories -- I. Exploring Small Scale Sequences of Psalms -- II. 'Seamingly' Important Psalms -- III. Mapping the Dead Sea 'Psalms' Scrolls -- C. Focal Points for the Current Study -- Chapter 2: The Elusive String -- A. Anthology Defined -- B. An Anthological Genre? -- C. Anthologies Unfold -- D. Uncovering the Artificial -- E. Outlining the Task at Hand -- Part II: Anthologies Compared -- Introduction -- Chapter 3: Artifactual Diversity -- A. Reconsidering Fixed Sequences -- B. Variation in Ancient Manuscripts -- C. Continuous Variation -- Chapter 4: Paratexts -- A. Prefaces -- B. Titles -- C. Colophons, Doxologies, and Epilogues -- Chapter 5: The How and the Why -- A. Collections with Few Manuscript Variations -- B. Collections with Manuscript Variation -- C. Collections without Ancient Manuscripts -- I. The Homeric Hymns -- II. The Psalms of Solomon -- D. The Question of Purpose Once Again -- I. Archival Economy -- II. Scribal Curriculum -- III. Preservation (Canonization) -- Overview and Outlook -- Part III: The Artifacts -- Introduction -- Chapter 6: Overview of the Scrolls -- A. Second Century BCE -- B. First Century BCE -- I. First Half or Middle of the Century -- II. Second Half of the Century -- C. The Turn of the Era -- D. First Century CE -- I. First Half of the Century -- II. Middle and Second Half of the Century -- Chapter 7: Evaluating the Evidence -- A. Reconstructing a 'Book' of Psalms? -- I. Preliminary Observations -- II. Arguments for the Stabilization of the 'Book' of Psalms -- III. Beyond Statistics -- 1. A Farewell to a Two-Stage Stabilization -- 2. Possible Ways Forward -- B. 11Q5 as a Competing Collection? -- I. Liturgical Clusters -- II. Text -- III. David and 11Q5.
A. Reconsidering Fixed Sequences -- B. Variation in Ancient Manuscripts -- C. Continuous Variation -- Chapter 4: Paratexts -- A. Prefaces -- B. Titles -- C. Colophons, Doxologies, and Epilogues -- Chapter 5: The How and the Why -- A. Collections with Few Manuscript Variations -- B. Collections with Manuscript Variation -- C. Collections without Ancient Manuscripts -- I. The Homeric Hymns -- II. The Psalms of Solomon -- D. The Question of Purpose Once Again -- I. Archival Economy -- II. Scribal Curriculum -- III. Preservation (Canonization) -- Overview and Outlook -- Part III: The Artifacts
Introduction -- Chapter 6: Overview of the Scrolls -- A. Second Century BCE -- B. First Century BCE -- I. First Half or Middle of the Century -- II. Second Half of the Century -- C. The Turn of the Era -- D. First Century CE -- I. First Half of the Century -- II. Middle and Second Half of the Century -- Chapter 7: Evaluating the Evidence -- A. Reconstructing a 'Book' of Psalms? -- I. Preliminary Observations -- II. Arguments for the Stabilization of the 'Book' of Psalms -- III. Beyond Statistics -- 1. A Farewell to a Two-Stage Stabilization -- 2. Possible Ways Forward
B. 11Q5 as a Competing Collection? -- I. Liturgical Clusters -- II. Text -- III. David and 11Q5 -- IV. Structure and Purpose -- V. Beyond 11Q5 -- Overview and Outlook -- Part IV: In Search of the Artificial -- Chapter 8: Psalms 1-2 as Preface -- A. The Psalms in Question -- I. Psalm 1 -- 1. A Brief Walkthrough -- 2. Meditating on the Torah -- 3. On What? -- 4. For What? -- II. Psalm 2 -- 1. A Brief Walkthrough -- 2. A Crux Interpretum -- III. Conclusions -- B. Combining Psalms 1-2 -- I. Integrated Readings of Psalms 1-2 -- II. Internal Evidence -- III. External Evidence -- 1. LXX -- 2. 4Q174
3. Acts 13:33 -- 4. Early Reception of Psalms 1-2 -- C. Evaluating the Evidence -- I. Towards a Definition -- II. Debunking Strict 'Prefatorialism' -- Introduction -- Chapter 9: Superscriptions -- A. Overview and Analysis -- I. 'Author' Designations -- II. 'Type' Designations -- III. Musical Directions and Indications of Use -- IV. 'Biographical' Notes -- V. Hallelujah -- VI. Psalms with No Superscription -- B. Conclusions -- I. Forming Collections of Psalms -- II. Fixation of Psalm Sequences -- III. Exerting Interpretive Control -- Chapter 10: Psalm 72:20 -- A. Attempted Solutions
B. Psalm 72:20 as a Frozen Colophon
Literaturverzeichnis: Seite 415-451
Leicht überarbeitete Fassung der Dissertation Lund University 2016, die unter dem Titel "Like a garden of flowers: a study of formation of the "Book" of Psalms" erschien
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, Textual; Bible -- Canon; Psalter; Psalmendichtung; Rhetorik; Musik; Lied; Hochschulschrift